The Static Modes: An alternative approach for the treatment of macro- and bio-molecular induced-fit flexibility - Brut, M.; Estève, A.; Landa, G.; Renvez, G.; Djafari Rouhani, M. (The European physical journal. E, Soft matter and biological physics, 2009)
We present a new competitive method for the atomic scale treatment of macromolecular flexibility called Static Mode method. This method is based on the “induced-fit” concept, i.e. it maps the intrinsic deformations of a macromolecule subject to diverse external excitations. The algorithm makes it possible to obtain a set of deformations, each one corresponding to a specific interaction on a specific molecular site, in terms of force constants contained in the energy model. In this frame, the docking problem can be expressed in terms of interaction sites between the two molecules, the molecular deformations being extracted from the pre-calculated Static Modes of each molecule. Some preliminary basic examples aimed at illustrating potential applications where macro- or bio-molecular flexibility is of key importance are given: flexibility inducing conformational changes in the case of furanose ring and flexibility for the characterization, including allostery, of poly(N-isopropylacrylamide)(P-NIPAM) active sites. We also discuss how this procedure allows “induced-fit” flexible molecular docking, beyond state-of-the-art semi-rigid methods.